U.K. and U.S. Trading of British Cross-Listed Stocks: An Intraday Analysis of Market Integration - Werner, Ingrid M.; Kleidon, Allan W. (Review of Financial Studies, 1996)
This article analyzes intraday patterns for U.K. and U.S. trading of British cross-listed stocks. For each market, the intraday patterns for these stocks closely resemble those of otherwise similar, non-cross-listed stocks. There is a 2-hour period each day when cross-listed stocks are traded both in New York and in London. This overlap is characterized by concentrated trading as private information, originating in New York, gets incorporated into prices in both markets. Cross-border competition for orderflow tends to reduce already declining spreads in London. By contrast, New York specialists maintain high spreads during the overlap. Overall, the evidence indicates that order flow for cross-listed securities is segmented.